Behaviour of wide reinforced concrete beam in shear - Al. Dymany, Haidar R. Hashim (2010)
Wide reinforced concrete beams were been used in buildings to reduce reinforcement congestion and floor heights for a required headroom. The beam in most of these cases is wider than that of the supporting columns. Consequently, their shear capacity might be effected and differ from that of conventional beams. This project report presents the test results of ten wide beam specimens in which their shear performances were studied. The influence of the support widths (100%, 50% and 25% of the beam width), the arrangement of flexural reinforcement across the beam width, and the presence of shear reinforcement in the forms of vertical links, were investigated. The test setup was made similar for all the specimens, two pointed load were distributed equally on the beam width, each at distance equal to 630 mm from the center of support, therefore, all the specimens failed in diagonal tension shear. The results showed that the narrow support has no effect on the shear strength of concrete and the influence of concentrating the flexural reinforcement within the support width has no significant effect on the shear strength of concrete. On the other hand, the links efficiency reduced by 80 % due to the narrow support, and the influence of concentrating the flexural reinforcement within the support width recovers their efficiency to 100 %.